(NrELQTIWISTSKAQ TEORIQ ATOMA (B/s - (NbRAUN(B, (NmIHAIL aLEKSANDROWI^s; (NgUR^UMELIQ(B, (NaLEKSANDR dAWIDOWI^s; (NsAFRONOWA(B, (NuLXQNA iWANOWNAs ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1984)
(NbIBLIOGR(B. 99 (NNAZW(B.s
Keywords: (NaTOMNAQ FIZIKAs